Post concrete work / Amir Hamzah Rashid Ridha - Rashid Ridha, Amir Hamzah (Universiti Teknologi MARA, Perak, 2019)
Post concrete was a very important part in construction, therefore this report will discuss the sequence work of post concrete after the casting work and removal of formwork. This report was conducted for 48-storey office tower located at Jalan lmbi, Bukit Bintang. The objective of this report is to know the sequence work of post concrete, identify concrete problems on site and to know the rectification work for post concrete. To ensure the quality of the concrete and avoid any incident caused by poor concrete condition in the future. This report will explain the right procedure of post concrete work and what kind of defect on concrete that usually appeared after the removal of formwork.